2022
DOI: 10.1111/cas.15586
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of comprehensive genomic profiling tests for advanced or metastatic solid tumor in clinical practice

Abstract: Previous clinical trials indicate that 10%–25% of patients received genomically matched therapy after comprehensive genomic profiling (CGP) tests. However, the clinical utility of CGP tests has not been assessed in clinical practice. We assessed the clinical utility of CGP tests for advanced or metastatic solid tumor and determined the proportion of patients receiving genomically matched therapy among those with common and non‐common cancers. From August 2019 to July 2020, a total of 418 patients had undergone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Numeric covariates were dichotomized according to standard reference values, while those without standard reference values were dichotomized in accordance with previous research or expert consensus. 3,7,37,38 For variables with missing data (BMI, neutrophils, hemoglobin, platelets, albumin, LDH, creatinine, total bilirubin, AST, and CRP), a multiple imputation was implemented under the missing at random assumption. 39 Multivariable logistic regression was estimated to assess the association of travel distance and time with genotype-matched trial participation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numeric covariates were dichotomized according to standard reference values, while those without standard reference values were dichotomized in accordance with previous research or expert consensus. 3,7,37,38 For variables with missing data (BMI, neutrophils, hemoglobin, platelets, albumin, LDH, creatinine, total bilirubin, AST, and CRP), a multiple imputation was implemented under the missing at random assumption. 39 Multivariable logistic regression was estimated to assess the association of travel distance and time with genotype-matched trial participation.…”
Section: Discussionmentioning
confidence: 99%
“…CGP testing was performed using hybrid capture-based targeted DNA sequencing with FoundationOne CDx (Foundation Medicine), the OncoGuide NCC Oncopanel System (Sysmex Corporation), in-house NGS testing, or in blood-derived cell-free DNA with FoundationOne Liquid CDx (Foundation Medicine) or Guardant360 CDx (Guardant Health) . All patients were referred to the NCCH following discussion by regional molecular tumor boards (MTB) comprising medical oncologists, pediatric oncologists, pathologists, bioinformaticians, genome researchers, and genetic counselors . In addition to reports from the inspection companies, the MTBs used reports containing clinical annotation and information regarding genotype-matched clinical trials from the Center for Cancer Genomics and Advanced Therapeutics national database …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of cases in which a new treatment is applied based on cancer genome pro ling, which collectively analyzes many genetic abnormalities (mutations, base substitutions, insertions/deletions, copy number abnormalities, rearrangements, fusions, etc. ), has been estimated between 10% and 20% of all patients [5][6][7]. There are higher frequencies of such cases outside of Japan; however, the present usefulness of cancer genome pro ling has not been fully con rmed here [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…their own data. 1 They showed that patients who received genomically matched therapy had a longer survival than those who did not.…”
mentioning
confidence: 99%